Referensi sebagai layanan, referensi sebagai tempat: sebuah tinjauan terhadap layanan refernsi di perpustakaan perguruan tinggi - Umi Kalsum (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
In a library a reference service should be able to give satisfaction to the users by answering the question by referring to the reference source. As a reference room should provide comfort to the users, so the users can use it as well as possible.Keywords: References Resources